2009
DOI: 10.1242/dev.039859
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning of secondary arbor development: the effects of the ecdysone receptor on the adult neuronal lineages of theDrosophilathoracic CNS

Abstract: The adult central nervous system (CNS) of Drosophila is largely composed of relatively homogenous neuronal classes born during larval life. These adult-specific neuron lineages send out initial projections and then arrest development until metamorphosis, when intense sprouting occurs to establish the massive synaptic connections necessary for the behavior and function of the adult fly. In this study, we identified and characterized specific lineages in the adult CNS and described their secondary branch pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…By contrast, the secondary neurons produced during the postembryonic neurogenic phase are much more homogeneous (Truman et al, 2004;Pereanu and Hartenstein, 2006;Brown and Truman, 2009;Zhou et al, 2009). As seen in Fig.…”
Section: Effects Of Notch On Neuronal Fates Of the Secondary Neurons mentioning
confidence: 88%
See 2 more Smart Citations
“…By contrast, the secondary neurons produced during the postembryonic neurogenic phase are much more homogeneous (Truman et al, 2004;Pereanu and Hartenstein, 2006;Brown and Truman, 2009;Zhou et al, 2009). As seen in Fig.…”
Section: Effects Of Notch On Neuronal Fates Of the Secondary Neurons mentioning
confidence: 88%
“…Lineage 15 makes exclusively motoneurons that project to the leg imaginal disc (Truman et al, 2004;Baek and Mann, 2009;Brown and Truman, 2009;Brierley et al, 2009). Removal of Notch results in a doubling in the size of this neuron cluster from 28±2 (n10) cells in control clones to 57±2 (n7) neurons in Notch null clones.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type LinA MNs mainly target the femur and tibia and have a complex dendritic morphology in the neuropil (Fig. 4A) (Baek and Mann, 2009;Brierley et al, 2009;Brown and Truman, 2009). In either Hox (Scr Antp Ubx) or hth mutant LinA clones, the surviving MN axons targeted the same region of the leg as did wild-type LinA clones.…”
Section: Defects In Axon Targeting Of Hox and Hth Mutant Leg Mnsmentioning
confidence: 99%
“…With regard to this possibility, it is noteworthy that developmental studies have demonstrated a significant role for EcR-mediated ecdysone signaling in neuronal remodeling during formation of the adult nervous system. [31][32][33][34] For example, when EcR-mediated ecdysone signaling is blocked during the remodeling of neurosecretory Tv neurons, filipodial activity and axonal sprouting are severely inhibited, resulting in adult Tv neurons with a significantly reduced, misshapen axonal arbor. 35 Thus, 20E is able to trigger and coordinate the molecular processes necessary for proper neuronal remodeling during development.…”
Section: Possible Involvement Of Chromatin Modifications In Ecdysone-mentioning
confidence: 99%